Peripheral artery disease: how much inter-leg symmetry? A contrast-enhanced magnetic resonance angiography study. Issue 16 (April 2020) - Secchi, Francesco; Di Leo, Giovanni; Delnevo, Alessandra; Alì, Marco; D'Angelo, Ida Daniela; Nardella, Veronica Gaia; Sardanelli, Francesco
Abstract : Abstract: The aim of this observational retrospective study was to qualitatively and quantitatively evaluate the symmetry of atherosclerotic plaques in patients with peripheral artery disease (PAD) undergoing contrast-enhanced magnetic resonance angiography of lower limbs. We retrospectively evaluated the peripheral magnetic resonance angiography of 82 patients considering the iliac, femoral and tibial arteries. Stenosis was scored 0 (none), 1 (<50%), 2 (50%–74%), 3 (75%–99%), and 4 (occluded). Symmetry was quantified as the percentage of bilaterally-diseased arteries and using the inter-leg absolute score difference (0–4). Signs test and Cohen κ were also calculated. Seventy-one (87%) patients had ≥1 bilaterally-diseased artery, and 168 (20%) of 820 artery pairs were bilaterally affected. At least 1 bilateral stenosis was observed from 11% (right internal iliac) to 73% (right superficial femoral). All 10 arteries showed symmetry, none of the inter-leg comparisons being significantly different ( P ≥ .100). Cohen κ ranged from 0.208 (common femoral) to 0.533 (internal iliac). This study showed that PAD was symmetrically distributed between the 2 legs, with the internal iliac artery being the most symmetric segment. Symmetry of PAD was quantified in 20%.